2014
DOI: 10.1002/bin.1396
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with Massed Versus Interspersed Trials: Effects on Acquisition, Maintenance, and Problem Behavior

Abstract: The current study evaluated the effects of teaching three programs using massed-trial teaching (MTT) versus interspersed-trial teaching (ITT) for three participants diagnosed with autism. Specifically, we compared the (i) rate of response acquisition, (ii) percentage of trials per session with problem behavior, and (iii) number of acquisition targets maintained following mastery. For all three participants, the rate of acquisition was higher under MTT than ITT, and levels of problem behavior were similar in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
(39 reference statements)
3
23
0
Order By: Relevance
“…As a whole, recent studies have not evaluated the effects of different TI ratios on engagement in escape‐maintained problem behavior during academic instruction. Henrickson et al () and Nicholson () found that TI and MTT were associated with comparable levels of problem behavior across participants; however, participants in both studies generally displayed low rates of problem behavior across conditions, and neither study included a functional analysis of the participants’ problem behavior during instructional periods. Volkert et al () implemented escape extinction during their TI and MTT conditions; however, they did not report data on problem behavior.…”
Section: Facilitating Response Acquisitionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a whole, recent studies have not evaluated the effects of different TI ratios on engagement in escape‐maintained problem behavior during academic instruction. Henrickson et al () and Nicholson () found that TI and MTT were associated with comparable levels of problem behavior across participants; however, participants in both studies generally displayed low rates of problem behavior across conditions, and neither study included a functional analysis of the participants’ problem behavior during instructional periods. Volkert et al () implemented escape extinction during their TI and MTT conditions; however, they did not report data on problem behavior.…”
Section: Facilitating Response Acquisitionmentioning
confidence: 99%
“…They found that tacts taught using MTT consistently required the fewest trials to meet the acquisition criterion. In a methodologically similar study, Henrickson et al () compared MTT to TI across three programs (i.e., receptive identification, tacting, and sorting) for three children with ASD. The authors found that neither TI nor MTT consistently produced faster acquisition for any of the participants.…”
Section: Facilitating Response Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, researchers have compared massed‐trial instruction, interspersed‐trial instruction, and varied‐trial instruction in the acquisition of target skills. In massed‐trial instruction, the instructor presents the same unmastered target stimulus on each trial throughout the session (e.g., Grow, Carr, Kodak, Jostad, & Kisamore, ; Henrickson, Rapp, & Ashbeck, ). In interspersed‐trial instruction, the instructor presents unmastered target stimuli interspersed with mastered stimuli that are similar (e.g., Dunlap, ; Neef, Iwata, & Page, ; Volkert, Lerman, Trosclair, Addison, & Kodak, ) or dissimilar (e.g., Volkert et al, ) to the unmastered target stimuli throughout the session.…”
mentioning
confidence: 99%